2002
DOI: 10.1007/s00114-001-0293-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structures and associations of humic substances in the terrestrial environment

Abstract: Here we show, for the first time, evidence of the primary molecular structures in humic substances (HS), the most abundant naturally occurring organic molecules on Earth, and their associations as mixtures in terrestrial systems. Multi-dimensional nuclear magnetic resonance (NMR) experiments show us that the major molecular structural components in the mixtures operationally defined as HS are aliphatic acids, ethers, esters and alcohols; aromatic lignin derived fragments; polysaccharides and polypeptides. By m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
165
0
14

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(194 citation statements)
references
References 22 publications
15
165
0
14
Order By: Relevance
“…The alternative presented was that humic substances were supramolecular associations of heterogeneous, relatively small molecules. Magnetic resonance tests confirmed that molecular aggregations of mixtures of variously sized humic substances occur in soils (Simpson et al 2002). Sutton and Sposito (2005) added the understanding that the molecular aggregations of humic substances include micellar structures, which are arrangements of organic molecules in aqueous solutions that form hydrophilic exteriors while containing hydrophobic interiors.…”
Section: Humic Acidsmentioning
confidence: 94%
See 1 more Smart Citation
“…The alternative presented was that humic substances were supramolecular associations of heterogeneous, relatively small molecules. Magnetic resonance tests confirmed that molecular aggregations of mixtures of variously sized humic substances occur in soils (Simpson et al 2002). Sutton and Sposito (2005) added the understanding that the molecular aggregations of humic substances include micellar structures, which are arrangements of organic molecules in aqueous solutions that form hydrophilic exteriors while containing hydrophobic interiors.…”
Section: Humic Acidsmentioning
confidence: 94%
“…Humic substances are end products of microbial decomposition and chemical degradation of dead biota in soils (Asli and Neumann 2010, Schiavon et al 2010) and are considered to be the most abundant naturally occurring organic molecules on earth (Simpson et al 2002) and the major components of soil organic matter (Nardi et al 2002). Interestingly, dissolved humic substances are common in freshwater bodies where they have been shown to interact with freshwater organisms, a topic reviewed by (Steinberg et al 2008).…”
Section: Humic Acidsmentioning
confidence: 99%
“…Based on their solubility in aqueous solution, HS are operationally divided into three different fractions: (i) humic acid (HA), the fraction soluble at alkaline pH values; (ii) fulvic acid (FA), the fraction soluble at all pH values; and (iii) humin, the fraction insoluble at all pH values (Swift, 1996). The newest concept attributed to HS is an association of molecular structures (100-2000 Da) with macromolecular characteristics resulting from aggregates formed by hydrogen bonding, nonpolar interactions, and polyvalent cation interactions (Piccolo, et al, 2002;Simpson et al, 2002). FTIR spectroscopy has been extensively used in the study of the composition, structure and functionalities of HS isolated from different ecosystems (Aguiar, et al, 2013;Baigorri, et al, 2009;D'Orazio and Senesi, 2009;Du and Zhou, 2009;Ferrari, et al, 2011;Francioso, et al, 2009;Senesi, et al, 2003;Stevenson, 1994;Tatzber, et al, 2008;Zhang, et al, 2011).…”
Section: Humic Substances Characterizationmentioning
confidence: 99%
“…On the one hand molecules can be stabilized in the soil by a range of processes, including (i) recalcitrance (molecules that require too much energy to decompose), (ii) inaccessibility to decomposition which includes the attachment of molecules to mineral surfaces and the spatial separation of decomposers and substrates (Sollins et al 1996;Torn et al 1997;Kaiser et al 2002;Kogel-Knabner 2002;von Luetzow et al 2006). On the other hand, molecules can be newly synthesized by soil organisms and mimic the stability of plant-derived molecules (Lichtfouse et al 1995;Gleixner et al 2001;Simpson et al 2002;Kelleher and Simpson 2006;Kindler et al 2006;Simpson et al 2007;Miltner et al 2009). Recalcitrance of chemical compounds is very obvious from oil and coal that originate from plant material and consist of lipids like alkanes and polyaromatic structures like polyaromatic hydrocarbons (PAH), respectively (Engel and Macko 1993).…”
Section: Soil Organic Mattermentioning
confidence: 99%